Optimization in Finite Elements to Define the Friction Factor Through Ring Compression Tests - Thomas G. Santos; André Rosiak; Diego R. Alba; Diego P. Wermuth; Lirio Schaeffer (Tribology in Industry)
The objective of this study was to evaluate the performance of a lubricant by defining the value of the friction factor at the interface. Ring compression tests were performed at room temperature for a typical steel in mechanical forming applications. The samples were compressed to 10%, 25% and 40% of their initial height with a constant speed of 3 mm/min. Using the FORGE NxT2.1 finite element software, an optimization procedure was carried out to reduce the computational cost, then simulations were performed by varying the values of the friction factor so that a cost function was minimized. The cost function for this optimization considers a relationship between the internal and external diameters of the specimens for the simulated and experimentally measured cases. The results showed a good relationship between experiments and numerical analysis. After the optimization was performed, the value of the friction factor m varied between 0.001078 and 0.0873, depending on the dimensional measurement method used.